Implementation Pathways for Vocational Education in Supporting the Cultivation of High-Quality Farmers - Chen, Zhizhong (Journal of Theory and Practice in Education and Innovation, 2025)
This paper aims to explore how vocational education can effectively promote the cultivation of high-quality farmers, thereby facilitating the modernization of agriculture and rural areas. First, it introduces the background of the study, highlighting the real issues of insufficient rural talent structure and the urgent needs of rural economic transformation, and elucidates the significant role of vocational education in addressing these challenges. Second, it discusses the concepts and characteristics of vocational education, as well as the connotations and requirements of high-quality farmers, emphasizing the close relationship between vocational education and the cultivation of high-quality farmers. Subsequently, it analyzes the problems and challenges faced by vocational education in farmer training, such as the disconnection between curricula and practical needs, the singularity of teaching methods, and insufficient industry alignment. Finally, it proposes implementation pathways for vocational education to support the training of high-quality farmers, including optimizing curriculum design, innovating teaching methods, and deepening industry integration.